SITEM PENENTUAN KELAS FAVORIT UNTUK SISWA TELADAN (Information Technology and Telematics, 2015)
Abstrak   :~~   Loireng   State   primary school is elementary school, there are several classes in one generation. To facilitate the grouping of students - students and perengkingan example, the SDN Loireng require an application for the provision of assessment for each - each student as a benchmark. This   research   was   conducted   with several stages of design and implementation. The design is how to make an application perengkingan,  while  the  implementation  of this application for SDN Loireng. Based on the test results on the application for information perengkingan Loireng SDN is an application perengkingan contains student data, teacher data, and ranking students. Keywords : ~~ranking, student, class